Identifying, assessing, and treating bipolar disorder at school - Hart, Shelley R.; Brock, Stephen E.; Jeltova, Ida. (New York : Springer, 2014)
'Identifying, Assessing, and Treating Bipolar Disorder at School presents child and education practitioners with an evidence-based framework for accurate identification, assessment, and intervention of bipolar disorder. This straightforward resource clears up misconceptions about the condition, and outlines its complex presentation in young people, where it may appear in tandem with other disorders and bring challenges to treatment. By providing information to assist in referrals, consultations, and recommendations for special education, the authors give the reader a unique vantage point for improving students' learning environment and helping to facilitate the work of fellow professionals. Among the topics: Prevalence and associated conditions. Case finding, screening, and referrals. Diagnostic and psycho-educational assessment Treatment of bipolar disorder in children and adolescents. Plus suggested resources to assist students and their families. Identifying, Assessing, and Treating Bipolar Disorder at School is an essential reference for school psychologists and allied educational professionals, special education teachers, speech and language therapists, counselors, clinical child psychologists, and mental health practitioners'--Back cover.
Buku Bacaan Asas Fakulti.
Includes bibliographical references (p. 139-158) and index.
Keywords: Manic-depressive illness in children; School psychology